THE USE OF ISLAMIC STORIES AS AN EFFORT TO IMPROVE STUDENTS' RELIGIOUS CHARACTER IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Ervina Ervina; Alfin Nurofikoh; Lenny Afriani; Muhammad Asroni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study explores the utilization of Islamic stories as an effective strategy to enhance the religious character of students in Islamic Religious Education (PAI). Storytelling, rooted in psychological and pedagogical theories, offers a meaningful and engaging learning approach that fosters moral and spiritual development. Teachers play a critical role in selecting relevant stories and applying diverse techniques supported by multimedia to maximize student engagement and comprehension. Despite challenges such as limited instructional time, scarcity of quality materials, and fluctuating student attention, technological advancements present promising opportunities for digital and interactive storytelling. The successful integration of Islamic stories in the curriculum requires well-designed educational frameworks, teacher competencies, and continuous reflection and evaluation to cultivate ethical and religious values effectively among students.